Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations II. ASSOCIATED CLINICS. Orthopaedic Surgeon-in-Charge - MR. NORMAN CAPENER, F.R.C.S. Chairman, Dist. Com. Hon. Clinic Sec. Clinic. Address. Day. Hour open. John Radcliffe, Esq., M.B.E. Miss Rowe, Deepdene, Exeter Hon. Sec. Dist. Com. : Mrs. Winckworth, Dunchideock House, Dunchideock. Exeter. Providence Chapel Lecture Hall, Northernhay Street. Tuesday (2nd & last).* 2.15 p.m. Dr. John Harper, Pilton Cottage, Barnstaple. Miss Mew, 35 Hills View, Barnstaple. Barnstaple. The Maternity and Infant Welfare Offices, Boutport Street. Friday (1st).* 11.30 a.m. Mrs. T. Phillips, J.P., Sudbury Lawn, Honiton. Miss Norman, St. Michael's Mount, Honiton. Honiton. Wesley Hall, New Street. Tuesday (2nd).* 10.30 a.m. Lady Seale, Slade, Nr. Kingsbridge. Mrs. Roberts, Staunton Lodge, Kingsbridge. Kingsbridge. Wesleyan Schoolroom, Fore Street. Friday (1st).* 11 a.m. Mrs. A. Williams, Werrington Park, Launceston. Mrs. Galbraith, The Priory House, Launceston. Launceston. Y.M.C.A., Wooda Road. Monday (1st).* 2.30 p.m. The Mayor (ex-officio). Mrs. Worden, West Bridge, Okehampton. Okehampton. Holsworthy Sub-Clinic. St. John's Mission Room. Monday (1st).* 11 a.m. Lt.-Col. Bastard, D.S.O., J.P., Kitley, Yealmpton. Miss Daukes, St. Andrew's Vicarage, Plymouth. South-Western at Plymouth (but excluding that city). Mutley Assembly Rooms. Monday (2nd).* 2.30 p.m. Lady Heathcoat-Amory, C.B.E., Knightshayes Court, Tiverton. Miss Waterworth, St. Aubyn Villas, Tiverton. { Tiverton. { Uffculme Sub- Clinic. The Maternity and Infant Welfare Offices, Hammett's Square. Thursday (1st).* 10.30 a.m. Dr. Dunlop, M.O.H., Torquay. Miss Mottram, Langdale, Headland Road, Livermead, Torquay Torquay. St. Marychurch Memorial Hall, Torquay Wednesday (2nd & 4th).* 11 a.m. Note.— The above are the only Orthopaedic Clinics in Devonshire and North Cornwall with which D.A.C.A. is in any way associated. *Surgeon attends. 292/841.51/2/2